Impact of COVID-19 on new pharmacotherapy for insomnia: A matched cohort study using the national insurance claims database in Japan - Daisuke Miyamori; Shuhei Yoshida; Wataru Omori; Saori Kashima; Masanori Ito (PLoS ONE, 2026)
Background The COVID-19 pandemic has profoundly affected impacted both physical and mental well-being. This matched cohort study investigated the effects of COVID-19 on pharmacological treatments for insomnia, using Japan’s National Insurance Claims Database. Methods Data were matched by age, sex, Charlson Comorbidity Index (CCI) score, and enrollment month. Incidence rate ratios (IRR) and incidence rate differences (IRD) were calculated and compared for insomnia medication initiation, and subgroups based on age and sex categories. Sensitivity analyses were conducted for segmented intervals of 0–4, 5–12, and after 12 months. Results The study included approximately 2 million pairs, predominantly women (59.4%), with a median follow-up of 7 months (Interquartile range, 4–12). Initiation of any insomnia medications occurred 77626 and 43142 times in the COVID-19 and control groups, respectively. IRR for new prescriptions was 1.7 times higher in the COVID-19 group (IRR: 1.71, 95% confidence interval [CI] 1.69–1.73), with an IRD of 1,634 events per 1,000,000 person-months (95%CI: 1599–1669). Non-Benzodiazepines and short-acting Benzodiazepines had the highest excess burdens among secondary endpoints. The risk was observed in all age categories, even in under 20 years (younger individuals: IRR: 1.46 95%CI 1.39–1.53, IRD: 380, 95%CI 333–427). Sensitivity analysis confirmed an increased risk over time, even after 12 months (IRD: 752, 95%CI 662–842). Conclusion COVID-19 significantly associates with an elevated risk of insomnia medication initiation, emphasizing the necessity for mental health support in post-COVID-19 care. This study offers insights into the pandemic’s influence on pharmacological treatment practices.